Macroeconomic Volatility and ETF Resilience During an Economic Recession Transition - Ariswati, Lusiana Desy; Filani, Libran (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the influence of key macroeconomic variables: interest rates, inflation, and gross domestic product (GDP), on the performance of exchange-traded funds (ETFs) in Indonesia from 2019 to 2022, spanning pre- and post-COVID-19 periods. Employing a quantitative econometric approach with time-series data and multiple linear regression analysis in Stata 17, the research tests hypotheses regarding these relationships using the Sharpe ratio as a risk-adjusted performance metric. Descriptive statistics reveal stable interest rates (average 4.35%) and inflation (2.68%), contrasted by high GDP volatility (standard deviation 3.003). Regression results indicate a positive but insignificant effect of interest rates (β = 0.101, p = 0.234), a significant positive impact of inflation (β = 0.170, p = 0.029), and an insignificant negative effect of GDP (β = -0.023, p = 0.377). These findings challenge conventional expectations, highlighting inflation's role in signaling moderate economic expansion that bolsters ETF returns in emerging markets during recovery phases. Notably, this positive inflation effect persists in broader contexts, as seen in Indonesia's sustained growth trajectory post-2022, where controlled inflation around 2.3% in 2025 complemented stable BI rates at 4.75% to support ETF resilience amid ongoing global pressures. The study addresses literature gaps by providing empirical evidence from Indonesia's transitional context, offering implications for policy and investment strategies amid global uncertainties, including recommendations for regulators to leverage moderate inflation for market stabilization.